Optimisation of Arthrospira Platensis harvesting using edible fungal bioflocculant - Hussin, Aimi Alina (2023)
Arthrospira sp. is considered a sustainable and completely natural microalgae-based food supplement to solve nutritional diseases, specifically malnutrition. However, both cultivation and harvesting methods for this microalgae takes up to 40% of energy consumption. Therefore, this study is aimed at maximizing Arthospira platensis biomass productivity under outdoor cultivation as well as propose safe and efficient harvesting method using edible fungi. Results from data obtained by comparing three types of photobioreactor (PBR) configurations conducted under indoor conditions demonstrated that macrobubble column (MA-CP) showed the highest dry cell weight yield compared to microbubble column (MI-CP) and airlift loop column (ALCP), with 0.536 ± 0.044 g/L, 0.477 ± 0.034 g/L and 0.274 ± 0.014 g/L, respectively. Thus, based on this result, MA-CP was carried out during the outdoor cultivation studies. Covered MA-CP showed a comparable but steady growth compared to non-covered MA-CP due to limited exposure of the microalgae to solar radiation. Whereas outdoor MA-CP PBRs resulted in significantly higher growth compared to indoor MA-CP due to the influence of temperature and light intensity. The result suggested that by taking advantage of Malaysia's weather conditions, integration of solar panel systems for outdoor cultivation of Arthrospira sp. in covered MA-CP is a viable and sustainable option. Meanwhile, a promising harvesting technique via bioflocculation is recommended as an alternative to conventional flocculation because of its simplicity and efficiency. In this study, Rhizopus microsporus was locally isolated and demonstrated the highest harvesting efficiency compared to other fungi. One-factor-at-time (OFAT) technique was used for the preliminary screening of different factors including mycelia concentration, pH of mycelia and temperature. The results were then applied in response surface methodology (RSM) modelling for optimization through central composite design (CCD). The harvesting efficiency (HE, %) for bioflocculation of A. platensis using R. microsporus was maximized (65.89 ± 2.795%) when 3.85% mycelial concentration (w/v) with initial pH of 2.5 at 38.8°C were used as the harvesting parameter conditions. Overall, the results showed that the overall process is viable and economical when the outdoor cultivation setup was integrated with solar panels as the system produced 2-fold biomass compared to the indoor cultivation coupled with harvesting microalgae step via locally isolated fungi as bioflocculant.